KAJIAN SEBARAN KADMIUM DALAM SAYURAN DAN TANAH DI BANTARAN SUNGAI CIKARANG BEKASI LAUT (CBL) - Alfandi Alfandi; Salaudin Djalal Tandjung; Bostang Radjagukguk; Narsito Narsito (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2010)
Contamination of contaminants in river are more due to human activities (antropogenic), such as the disposal of industrial waste and domestic waste. One type of inorganic pollutants that is toxic to living organism including human is cadmium (Cd). The movement of Cd in river water into the soil along the river is naturally and by human activity. The objectives of this study was to examine the distribution of Cd in soil on the river banks of the Cikarang Bekasi Laut (CBL) river, in Bekasi West Java, based on the distance from the pollutant sources during rainy and dry season (spatially and temporally). This study used a survey method in sampling plants, water and soil. Sampling was conducted at 10 sites and 10 observation times (dry and rainy season). The analyses of Cd content were conducted on plant, water and soil samples. In addition, pH was also measured in soil and water samples. Vegetable samples were collected from the field were kale, spinach and caisin. Statistical analyses comparized of analyses of variance (F test), comparatine analyses of the mean and correlation analyses. The results showed that the contents of Cd in the soil samples that close to the surface of the river water were higher than those of other soil samples. This was caused by the movement of Cd from the river water naturally due to changes in water level or river discharge fluctuation, as a consequence of changes in dry and rainy seasons. At sites further from the river (on land of cultivation), the presence of Cd in soil was mainly due to the use of river water for irrigation. Watering plant was mostly done during the dry season, at which the concentration of Cd in river water was relatively higher. The content of Cd in plant tissue (Spinach, kale and caisin) had a positive correlation with the content of Cd in the soil. The average content of Cd from the three plants were spinach > kale > caisin, consecutively. Keywords: antropogenic, cadmium (Cd), Cd uptake, pollution, riverbanks